Locus of Control Analysis in the Selection of Advanced Studies for Junior High School Students - Rulinawaty Rulinawaty; Dian Wardiana Sjuchro; Reza Saeful Rachman; Eza Aldonna (STAI Hubbulwathan Duri, 2022)
This study aims to determine the locus of control of junior high school students in the selection of further studies. This research method uses a descriptive quantitative survey with questionnaire and interview data collection techniques. The population of this research is 310 students and the sample is 108 students. The collected data is then analyzed using category percentages. The results of this study showed that 105 students (97%) got the results of internal locus of control where they had the will and responsibility for themselves in the selection of further studies, 2 students (2%) got the results of external locus of control where they lacked initiative. and only following the will of the people around them in the selection of further studies, and 1 student (1%) who has the same locus of control results between internal and external, in this case students who have the same locus of control results are students who do not have a desire to further study but still want to be the same as his other friends.